Effectiveness of Ureteroscopy-Assisted Retrograde Nephrostomy (UARN) for Percutaneous Nephrolithotomy (PCNL) - Kawahara, Takashi; Ito, Hiroki; Terao, Hideyuki; Kato, Yoshitake; Uemura, Hiroji; Kubota, Yoshinobu; Matsuzaki, Junichi (PLOS ONE, 2012)
Objective To determine the impact of ureteroscopy-assisted retrograde nephrostomy (UARN) during percutaneous nephrolithotomy (PCNL). Materials and Methods From April 2009 to September 2011, a total of 50 patients underwent PCNL for large renal stones (stone burden >2 cm). We performed UARN in the Galdakao-modified Valdivia position for 27 patients (UARN PCNL) and ultrasonography-assisted percutaneous nephrostomy in the prone position for 23 patients (prone PCNL). Results UARN PCNL significantly improved the stone-free rate (81.5% vs 52.2%) and the rate of residual stones (<4 mm, 92.6% vs 65.2%, P<0.05). The median length of the operation was significantly shorter for UARN PCNL, at 160 min, compared to 299 min for prone PCNL (P<0.001). There was one intraoperative complication in prone PCNL, namely a hemorrhage that resulted in stopping the initial treatment, but it was cured conservatively. The postoperative complications included a high grade fever that persisted for three days in two UARN PCNL patients (7.4%) and six prone PCNL patients (26.1%). The Clavien grading scores showed significantly lower postoperative complications for UARN PCNL compared to prone PCNL. Conclusion UARN is associated with a higher stone-free rate, shorter operation time, and fewer complications during PCNL than prone PCNL.